Impact of Front Line Demonstrations on Productivity Enhancement of Cluster bean in Arid Zone (Indian Journal of Extension Education, 2018)
The study was conducted in Bheenjwdia village of Jodhpur district of Rajasthan by ICAR-Central Arid Zone Research Institute, Jodhpur during 2010 to 2014 to study the Impact of Front Line Demonstrations on Productivity Enhancement of Cluster bean. The data were collected from 96 farmers and analysed. The results of the study showed that the yield under demonstration was 32.71 per cent higher as compared to farmers’ practices. The net returns and B: C ratios on demonstration plot were higher, i.e., ` 24234 and 2.41 respectively as compared to farmer’s practices (` 17160 and 1.96). The study suggests that for strengthening linkages with line department and converging the demonstration with Government schemes for large scale adoption of farmers’ fields this can be a good option for enhancing farmers’ income.